The Nurses’ Role in Handling Increased Intracranial Pressure for Hemodinamic Stats in Head Injury Patients (International Journal of Nursing Education, 2020)
Background: Head injury is a major matter of death and disability at a young or productive age. Theprevalence of head injuries has occurred and increased. The incidence of head injuries in the world wasreported 29,770 cases. A head injury produces intracranial haemorrhage, following the increased intracranialpressure. The increased intracranial pressure changes the hemodynamic status in the body. The treatment ofincreased intracranial pressure needs to be conducted immediately to avoid a bigger impact.Purpose: This review is to determine the handling management of intracranial pressure elevation forhemodynamic status in head injury patients.Method: The article adopted a systematic review. The identification of literature was performed by searchingjournal articles that have been published in 2009-2019 within databases such as Proquest, EBSCO, ScienceDirect, and Pubmed. The search was using keywords : nurse handling, intracranial pressure, hemodynamicstatus and, head injury. The selected articles that were decided by a combination of PRISMA flow diagramswith the Joana Brigg Institution (JBI) checklist obtained 16 corresponding articles.Result and Discussion: The management of intracranial pressure such as positioning, hypothermiamanagement, and ventilation control as well as medical actions such as adequate oxygenation, drainageaction, diuretic and hyperosmolar therapy, blood sugar control, and decompressive craniectomy.Conclusion: Management of increased intracranial pressure for hemodinamyc status in head injury patientsconsists of positioning, oxygenation, hyperventilation, drainage, diuretic therapy, hypothermia management,blood sugar control, decompressive craniectomy